(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2024)
Background. Knee replacement surgery is a standard treatment that relieves the problems caused by advanced knee osteoarthritis. Postoperative rehabilitation programs are extremely important because they can improve knee function and reduce pain in patients after EP surgery. The aim. To assess the effect of visual feedback on knee joint function and pain in patients who underwent arthroplasty. Methods. The study involved 30 women experiencing pain after knee replacement surgery. Subjects were randomly divided into two groups: experimental (n = 15) and control (n = 15). Patients in both groups received one hour of physical therapy every day from Monday to Saturday. The patients of the study group performed 30 minutes of conventional physiotherapy in the hall, which includes exercises for increasing the range of motion of the knee, increasing strength and endurance, and 30 minutes of gait and balance training supplemented with visual feedback. The patients in the control group received regular physiotherapy in the hall lasting 60 minutes. The duration of the study is three weeks. Knee joint pain, range of motion, leg extensor and flexor muscle strength, and body balance were evaluated. Results. Both physical therapy programs significantly reduced knee pain and improved knee function. The control group’s pain decreased by 63.4 percent, while the experimental group’s pain decreased by 60.8 percent. The knee joint flexion amplitude improved by 42.9 percent in the control group and 43.4 percent in the experimental group. The improvement in the knee joint flexion amplitude was 88.3 percent in the control group and 92.7 percent in the experimental group. In the control group, the strength of the calf extensor muscles increased by 30.0 percent, and in the experimental group, it increased by 34.23 percent. The strength of the calf flexor muscles increased by 29.4 percent in the control group and 34.2 percent in the study group. Balance and gait indicators, according to the Tinetti scale, improved statistically significantly in the control group by 27.6 percent, and in the study group by 45.1 percent. In the study group, only balance and gait were better after the interventions (p<0.05) than in the control group. Conclusion. Both interventions: conventional physical therapy and supplemented with visual feedback significantly improved the subjects’ functionality and reduced knee pain. Physiotherapy with visual feedback was more effective than conventional physiotherapy in recovering balance and gait in subjects after knee arthroplasty. Keywords: knee arthroplasty, exercises, visual feedback.